Determinan Keputusan Petani Mengelola Usahatani Padi Di Lahan Suboptimal - Adistya, Adilla; Nurmalina, Rita; Tinaprilla, Netti (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2024)
The conversion of paddy fields seriously impacts rice availability for national food reserves, so the government is implementing a sub-optimal land extension program. Indonesia has sub-optimal land that has the potential to become a national rice barn if appropriately managed. The types of sub-optimal land most widely used in rice cultivation are lowland and tidal swamps, where the community can work. This research analyzes the determinants of rice farmers' decisions in managing sub-optimal land. This research was conducted in West Tanjung Jabung Regency, Jambi Province, with a sample of 90 rice farmers. Data were analyzed using the multinomial logistic regression method. The determining factors are seen from the demographic and economic aspects. The research results show that factors that significantly influence farmers' decisions to choose tidal land from the demographic aspect are age and farming experience; from the economic element are the number of family dependents, land ownership status, and non-farming income. The significant determining factors in farmers' decisions to manage lowland swamp land from the demographic aspect are age and farming experience, and from the economic element are the number of family dependents and non-farming income. From the research, recommendations that can maximize the use of sub-optimal land are increasing promotion and education to the community about rice cultivation on sub-optimal land, providing easy access for farmers to rent land, and it is hoped that farmers will continue to have non-farming income to balance household needs and procurement of capital and farming input.